Vaginal microbiota of pregnant women with Ureaplasma urealyticum and Mycoplasma hominis infections - Oh, Kwan Young; Lee, Sunghee; Park, Jaewan; Park, Mi Hye; Jeong, Ji Hun; Yang, Jung Bo; Lim, Chul Kwon; Ha, Joong Gyu; Yang, Yun Seok (Frontiers in Cellular and Infection Microbiology, 2024)
BackgroundThe association between preterm birth and Mycoplasma species such as Mycoplasma hominis and Ureaplasma urealyticum has been extensively investigated. In a clinical setting, conventional diagnostic methods for them involve culture methods for Mycoplasma spp. and Ureaplasma spp., along with PCR tests. However, the clinical utility of these tests remains controversial, highlighting the necessity for more robust and reliable methods for identifying and understanding Mycoplasma infections.ObjectiveThis study aimed to assess the distribution of microbiota in pregnant women with Mycoplasma hominis and Ureaplasma urealyticum infection by the comparison of conventional diagnostic methods with vaginal microbial community analysis.Study DesignThis prospective case–control study involved 228 Korean pregnant women and utilized vaginal microbial community analysis, Ureaplasma/Mycoplasma culture, and 12-multiplex PCR for sexually transmitted diseases. Cross-correlation analysis in SPSS 27 compared the results of two conventional methods with vaginal microbial community analysis. R software generated box plots depicting the relative abundance of microorganisms. Network analysis was conducted using Cytoscape.ResultsPositive Ureaplasma urealyticum culture findings were observed in 60.2% of patients, with 76.4% positive for Ureaplasma parvum PCR and 13.2% positive for Ureaplasma urealyticum PCR. Mycoplasma hominis culture was positive only in two patients, while Mycoplasma hominis PCR was positive in eight women. Vaginal microbial community analysis identified significant differences in relative abundances of Gardnerella species type I and Fannyhessea vaginae between the Ureaplasma urealyticum PCR positive and negative groups. Mycoplasma hominis PCR positive patients exhibited significant differences in 11 bacterial species, including Gardnerella species I and Fannyhessea vaginae.ConclusionThis study suggests that STD-PCR may be more accurate than Ureaplasma/Mycoplasma culture for the diagnosis of Mycoplasma hominis and Ureaplasma urealyticum infection. Also, the presence of Gardnerella species I and Fannyhessea vaginae implies their potential influences on Ureaplasma urealyticum and Mycoplasma hominis infections based on results of vaginal microbial community analysis. Therefore, vaginal microbial community analysis may give the more information of their pathophysiology.